1994
DOI: 10.1080/09553009414550991
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Radiation-induced Apoptosis in the Cerebellum of 14-day-old Rats after Acute or during Continuous Exposure

Abstract: We have studied, by histological methods, cytological progression, frequency and distribution of apoptosis in the external granular layer of the cerebellum after whole-body irradiation of 14-day-old rats by gamma-rays from 60 Co. After acute exposure to 0.25, 0.5, 1.5 and 3 Gy (18 cGy/min), the duration of the apoptotic process gradually increased with dose from 6-9 h after 0.25 Gy, to > 24 h after 3 Gy. Up to 1 Gy, maximal frequency was found 6 h after exposures, and at this postirradiation time a linear incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Moreover, the absorption and oxidative metabolism of stevioside in humans is analogous to that of rats [20]. These dark neurons might be a result of neuronal degeneration [28]. The ages studied ranged from 3 months (age of administration) to 9 months (age of sacrifice) according to the established classification of Bello-Pineda et al [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the absorption and oxidative metabolism of stevioside in humans is analogous to that of rats [20]. These dark neurons might be a result of neuronal degeneration [28]. The ages studied ranged from 3 months (age of administration) to 9 months (age of sacrifice) according to the established classification of Bello-Pineda et al [27].…”
Section: Discussionmentioning
confidence: 99%
“…Observations in vivo have shown that both granule cells and astrocytes undergo apoptosis in the rodent postnatal cerebellum (Krueger et al, 1995;Wood et al, 1993). Apoptosis of granule cells in vivo also occurs in mutant mice (Migheli et al, 1995a;Murtomä ki et al, 1995;Wü llner et al, 1995) and after experimental X-ray irradiation (Fritsch et al, 1994;Wood and Youle, 1995).…”
mentioning
confidence: 99%
“…Ionizing radiation can induce apoptosis, and cause apoptosis as low as 0.25 Gy. 28 In vivo experiments, TUNEL immunofluorescence staining showed that compared with that of the Control group, the apoptosis rate was significantly increased in the DMSO + R group, indicating that the radiation induced apoptosis of brain cells of mice. Compared with the DMSO + R group, the apoptosis rate of the AS-IV pretreatment re-radiation group at a concentration of 40 mg/kg was significantly decreased, suggesting that AS-IV at a concentration of 40 mg/ kg can effectively inhibit radiation-induced brain cell apoptosis.…”
Section: Discussionmentioning
confidence: 94%